PTU-037 Cryoballoon therapy is effective in the treatment of patients with refractory oesophageal neoplasia after unsuccessful first line endoscopic eradication therapy. (17th June 2017) - Alzoubaidi, D; Magee, C; Graham, D; Lovat, L; Haidry, R
Abstract : Introduction: Endoscopic eradication therapy EET with endoscopic mucosal resection EMR for visible lesions followed by Radiofrequency ablation RFA for flat Barrett's oesophagus BE is the gold standard treatment for patients with BE related neoplasia. EMR and ESD are effective in the eradication of early squamous cell neoplasia ESCN. The efficacy of EET is favourable with reported eradication rates of dysplasia CR-D and intestinal metaplasia CR-IM in BE of over 90% and 80% respectively. In a minority of patients EET is unsuccessful and alternative therapies are desirable. Cryoablation with the Cryoballoon device (C2 therapeutics) is a novel ablative therapy that uses cycles of freezing and thawing to induce cell death by intra and extracellular ice formation, vascular injury, and apoptosis. Aim: Single centre study to evaluate the feasibility of the focal cryoablation for the treatment of areas of refractory oesophageal neoplasia in patients who had undergone first line EET. Endpoints were CR-D and CR-IM in those with BE related neoplasia. The rate of stenosis and adverse events were also studied. Method: A total of 10 cases (7male, 3female; mean age=71; range:55–83) were treated by a single experienced endoscopist. Baseline histology included 3 Low Grade Dysplasia LGD, 5 High Grade Dysplasia HGD, 1 Intramucosal cancer (IMC) and 1 patient with ESCN. The mean length of dysplastic BE treated was 3 cm (Range: 1–9) in 9 cases and 4 cm of a visible lugols-voiding-mucosa in 1 patient with ESCN. An average of 9 ablations applied per patient; range 2–22. Each selected area of visible dysplasia received 10 s of ablation. Only 1 session of cryoablation per patient. Endoscopy and re-biopsy from the treated sites were taken at 3 months post ablation to assess for end points. Results: CR-D achieved in 70% (7/10) of all patients. In those with BE the CR-D was 78% (7/9) and CR-IM 44% (4/9). The patient with ESCN did not respond to Cryoablation and was referred for radiotherapy. There was progression from LGD to HGD in 1 BE case that was treated with EMR. Technical difficulty due to challenging anatomy was noted in 1 case with tortuous and dilated oesophagus. There were no device malfunction or adverse events. There was no recorded stenosis post procedure. Conclusion: In this feasibility study, Cryoablation with the cryoballoon device appears to be a good option in patients with refractory neoplasia after sequential first line EET. It is well tolerated and partially successful in obtaining CR-D and CR-IM in "treatment-refractory" patients with BE dysplasia. Further trials of dosimetry, efficacy and safety in "treatment-naïve" patients with randomised controlled trials is recommended and are underway. Disclosure of Interest: None Declared